How Much Does an Increase in Oil Prices Affect the Global Economy? Some Insights from a General Equilibrium Analysis - Timilsina, Govinda R. (World Bank, Washington, DC, 2013)
A global computable general equilibrium model is used to analyze the economic impacts of rising oil prices with endogenously determined availability of biofuels to mitigate those impacts. The negative effects on the global economy are comparable to those found in other studies, but the impacts are unevenly distributed across countries/regions or sectors. The agricultural sectors of high-income countries, which are relatively energy intensive, would suffer more from rising oil prices than would those in lower-income countries, whereas the reverse is true for the impacts across manufacturing sectors. The impacts are especially strong for oil importers with relatively energy-intensive manufacturing and trade, such as India and China. Although the availability of biofuels does mitigate some of the negative impacts of rising oil prices, the benefit is small because the capacity of biofuels to economically substitute for fossil fuels on a large scale remains limited.